MON-434 Encapsulated Follicular-Variant of Micropapillary Carcinoma Presenting with Distant Bony Metastasis - Berlioz, Ana Ramirez (J Endocr Soc, 2020)
INTRODUCTION The incidence of thyroid cancer has risen steadily over the last decades, in part due to increasing diagnosis of apparently low-risk well-differentiated cancers. The outcomes of well-differentiated thyroid cancers, including follicular variant papillary thyroid carcinoma (PTC), are believed to be quite favorable, with a largely indolent benign course. We examine an encapsulated follicular-variant of micropapillary carcinoma presenting with distant bony metastasis. CASE 55-year-old lady presented to clinic after biopsy of iliac crest (IC) mass revealed thyroid tissue. One year prior she started having dull pain at right hip, attributed to increased physical activity. She noticed a tender “lump” on her right hip. CT revealed destructive right iliac 8 cm mass with extraosseous soft tissue component, central necrosis, and eccentric calcifications; and right ovarian cyst. Right IC biopsy was consistent with thyroid tissue with positive Thyroglobulin and TTF-1 immunostains. Physical exam was normal, except for mild tachycardia, hypertension, right flank large rounded mass fixed to IC, tender to palpation without erythema or warmth on overlying skin. Thyroid ultrasound showed normal thyroid gland except 5.58 x 6.22 x 7.76 mm left lobe nodule without increased vascularity but with coarse peripheral calcification. FNA was unsatisfactory. Thyroid function tests revealed undetectable TSH, elevated FT4, FT3, and markedly elevated thyroglobulin and TSI. PET/CT scan showed focal area of mild FDG avidity, corresponding to the right iliac crest mass, without additional areas of FDG avidity suggestive of metastatic disease or primary neoplastic process. Three weeks after presentation, patient began having symptoms of hyperthyroidism. As FT4 and FT3 continued to rise, she was started on propranolol and methimazole. Due to inadequate response, methimazole was switched to high dose propylthiouracil with mild improvement. Thyroid uptake and scan and SPECT-CT revealed increased thyroid uptake and thyromegaly consistent with Graves’ disease and redemonstrated large right IC lesion with increased uptake in the periphery and central photopenia, suggesting metastatic thyroid malignancy. Pathology from total thyroidectomy reported encapsulated follicular variant of PTC, confined to the left lobe of the thyroid, without extrathyroidal extension, greatest tumor dimension 0.6cm. As metastasis to the IC were unlikely to have originated from this small encapsulated thyroid cancer, it was recommended to proceed with right oophorectomy for suspected malignant struma ovarii and IC lesion debulking. Surgical pathology revealed right ovary and fallopian tube without pathologic changes or features of teratoma and tissue from right iliac mass consistent with PTC. Patient is off all antithyroid medications and remains biochemically euthyroid, awaiting radioactive iodine therapy.